2017
DOI: 10.1037/mgr0000049
|View full text |Cite
|
Sign up to set email alerts
|

Adapting simulation responses from judgment-based to analytic-based scores: A process model, case study, and empirical evaluation of managers’ responses among a sample of managers.

Abstract: Alyssa Mitchell Gibbons helped design the specific simulation exercise that was analyzed in the research, but before this project was conceived, and in no way stands to gain financially from the results of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…There have been a handful of studies that directly compare individuals who played with a team to individuals who played alone in a training setting [13][14][15][16][17]. A similar stream of research has reported on the positive impact that teamwork can have on individual outcomes [18,19].…”
Section: Human Interactionmentioning
confidence: 99%
“…There have been a handful of studies that directly compare individuals who played with a team to individuals who played alone in a training setting [13][14][15][16][17]. A similar stream of research has reported on the positive impact that teamwork can have on individual outcomes [18,19].…”
Section: Human Interactionmentioning
confidence: 99%